Analisis Kekuatan Struktur Pada Desain Traction Rod Lokomotif Kereta Api Dengan Metode Finite Element Analysis (FEA) - Irsad Makhbulloh Ilyasa; Ignatius Aris Hendaryanto; Handoko; Agustinus Winarno (Proklamasi 45 University, 2024)
The structural strength of locomotive bogies is crucial for bearing operational loads and absorbing engine vibrations to efficiently transmit torque to the train wheels. The traction rod, a critical component in this system, plays a key role in transferring power from the main engine to the locomotive wheels. With the CC300 locomotive engine producing 2.200 hp, the traction rod experiences significant loads, necessitating regular maintenance. Given that this component is currently imported, the company is striving to redesign the traction rod to ensure strong structural integrity for local production, reducing dependency on imports and optimizing maintenance costs. The redesign involves adding structures to the existing design to even out stress distribution and enhance safety factors. Finite Element Analysis (FEA) is utilized to compare the structural strength between the original and redesigned designs, resulting in significant improvements in load-bearing capacity and deformation reduction. Simulation results show variations in stress, deformation, and safety factors among the original design, the redesign by the company, and the redesign by the researchers. The original design exhibits a stress of 194,64 MPa, deformation of 4,2817 mm, and a safety factor of 1,2844. The company's redesign achieves a stress of 438,37 MPa, deformation of 3.4356 mm, with a safety factor of 0,5703. Meanwhile, the researchers' redesign shows a stress of 154,05 MPa, deformation of 4,4812 mm, and a safety factor of 1,6288.